Teenage Mutant Ninja Turtles : Jennika - the fifth turtle. - Eastman, Kevin; Curnow, Bobby; Waltz, Tom; Revel, Brahm; Pattison, Ronda (Teenage Mutant Ninja Turtles, 2024)
The newest member of the TMNT team, Jennika, embarks on her own adventures in these standalone stories!First, relive the events that led up to Jennika’s mutation into a Turtle. Then, as she tries to acclimate to life as a mutant, she must come to terms with both her troubled past and conflicted present. In search of a dangerous procedure to reverse her mutation, Jennika is tempted by the call of her old life. Then, mutants begin turning into monsters and spreading fear in Mutant Town. Jennika takes to the underworld to get to the bottom of the situation, but enemies old and new await!